Hakikat Kekuasaan Dalam Lakon Wahyu Purba Sejati Karya Ki Seno Nugroho - Afifudin Siti As`ari; Darmoko Darmoko (Kawruh : Journal of Language Education, Literature and Local Culture, 2022)
This paper discusses the essential of power in the wayang play entitled Wahyu Purba Sejati by Ki Seno Nugroho. There are quite a number of wayang kulit purwa plays with the theme of revelation, such as: Wahyu Makutharama, Wahyu Purba Kayun, Wahyu Darma, Wahyu Pancadarma, and others. One of wayang kulit purwa play that is unique in the last decade is Wahyu Purba Sejati play, presented by Ki Seno Nugroho. The power in this play is divided into four, namely Cahyaningrat, Reksakaningrat, Yuwananingrat, and Wimbaningrat. How the essential of power is constructed in the play Wahyu Purba Sejati by Ki Seno Nugroho is the main problem in this research. Creswell's qualitative method and Benedict Anderson's theory of power are used to analyze this issue of power. The study resulted in the finding that the concept of power in the play Wahyu Purba Sejati essentially refers to the gift of God's supernatural power given to humans who like to do inner work in a quiet place in their orientation to create world peace. Power is knowledge that contains subtleties, achieved through athe process of implementing self-control which functions to maintain world harmony by eradicating chaos, injustice and unrighteousness, in order to create a safe, peaceful, prosperous life. This study concludes that power is cosmic and magical (supernatural) which is represented by the acquisition of revelation as a manifestation of the achievement of certain social strata (wahyu kraton, wahyu patih, wahyu wahdat, and wahyu induk). Power is not only a tool that has the potential to be destructive, but it can also potentially be a means to meddle hayuningbawana (seek world peace).